The EU's new communication policy: After the failure of the constitutional treaty, now Plan D? - Katharina Gröber; Sabine Riedel (Stiftung Wissenschaft und Politik (SWP), 2005)
In mid-October 2005 the EU Commission reacted to the referenda that have failed for the time being in France and the Netherlands: Despite its further support for the European Constitutional Treaty the Commission deems it necessary to insert a period of reflection until mid-2006. All European institutions are supposed to use this breathing space to enter into a dialogue about common political aims with the citizens of the EU member states. Specific steps in this direction have now been presented in the form of the so-called Plan D by the EU Commissioner for communication, Margot Wallström. In order to strengthen the European identity in the sense of the Amsterdam Treaty, national debates about the future of Europe are to be set in motion following the motto 'democracy, dialogue and discussion'. However, the time period for this is very limited: The first results are already expected at the next Europe Day on May 9, 2006. (SWP-Comments / SWP)
Keywords: 320